Analysis of a maternal health medicines pipeline database 2000–2021: New candidates for the prevention and treatment of fetal growth restriction. (5th February 2023) - Lim, Shao; McDougall, Annie R. A.; Goldstein, Maya; Tuttle, Andrew; Hastie, Roxanne; Tong, Stephen; Ammerdorffer, Anne; Rushwan, Sara; Ricci, Christina; Gülmezoglu, A. Metin; Vogel, Joshua P.
Abstract: Objective: The Accelerating Innovation for Mothers project established a new database of candidate medicines under development between 2000 and 2021 for five pregnancy‐related conditions, including fetal growth restriction. The objective was to assess medicines for fetal growth restriction and their potential for clinical use globally. Design: Landscape analysis. Setting: Global (focus on low‐ and middle‐income countries, LMICs). Sample: Drugs, dietary supplements and biologics under investigation for prevention or treatment of fetal growth restriction. Methods: A research pipeline database of medicines was created through searching AdisInsight, PubMed and various grant and clinical trial databases. Analysis of clinical and preclinical candidates were descriptive. Main Outcomes Measures: Fetal growth restriction candidates in clinical development were identified and ranked as high, medium or low potential based on prespecified criteria, including efficacy, safety and accessibility. Results: Of the 444 unique candidates in the database across all five pregnancy‐related conditions, 63 were for fetal growth restriction. Of these, 31 were in clinical development (phases I, II or III) and 32 were in preclinical development. Three candidates, aspirin, l ‐arginine and vitamin D, were ranked as having high potential as preventive agents. There were no high‐potential candidates for treating fetal growth restriction, although five candidates were ranked as having medium potential: allylestrenol, dalteparin, omega‐3 fatty acids, tadalafil, and United Nations International Multiple Micronutrient Antenatal Preparation (UNIMMAP). Conclusions: l ‐Arginine, aspirin and vitamin D are promising, high‐potential preventative agents for fetal growth restriction. Based on the medicines pipeline, new pharmacological agents for fetal growth restriction are unlikely to emerge in the near future.